UNCONVENTIONAL MEASURES OF MONETARY POLICY: EXPERIENCE OF THE FEDERAL RESERVE SYSTEM OF THE UNITED STATES - Dzyublyuk, Oleksandr (Journal of European Economy, 2018)
The preconditions, causes and peculiarities of the global financial and economic crisis created the basis for the withdrawal of central banks from their traditional limited range of instruments of monetary influence on the economy and the transition to the active use of unconventional monetary policy measures. The Federal Reserve was the first central bank which used the unconventional measures of monetary policy as a key factor in overcoming the recession and bringing the US economy to a sustainable growth path. The traditional instruments of monetary regulation during the period of aggravation of financial crisis on the money markets turned out complete ineffective, that had the destructive consequences for the economy. That is why so important is the analysis of the reasons for this ineffectiveness and the necessity of use of unconventional instruments. The practical mechanism of using such unconventional instruments of the Fed includes such as large-scale asset purchases and FOMC’s forward guidance about intentions. And it is hard to underestimate the role of these tools in the withdrawal of the American economy from the state of recession. Also important are innovative credit policy programs that have been used by the Federal Reserve during the period of growing crisis, in terms of increasing the effective ness of its impact on the financial stabilization of the banking system, providing markets with liquidity and stimulating domestic demand. The use of unconventional monetary policy instruments aims to achieve a wide range of strategic goals that include not only price stability but also economic growth and low unemployment. Thus, based on the powerful influence of the Fed’s monetary policy on the dynamics of the main economic parameters, it is expedient to apply a dual mandate in formulating the strategic goals of the central bank. JEL: E44; E50; E52; E58; G21.